Web-Based Master Student Project Evaluation and Management System - Song, Ng Kar; Wahid, Juliana (Multidisciplinary Applied Research and Innovation, 2022)
Project in Computing is one of the core courses in Master of Science (Information Technology) (MSc. (IT)), School of Computing (SOC), Universiti Utara Malaysia (UUM). It is a platform where students can showcase the knowledge and skills they obtained during classes by implementing a project. The current practice of Project in Computing evaluation is through manual procedure which the submission of proposal and article to the evaluators were through email. There is no system to help the coordinator, evaluators, and supervisors in managing the evaluation process of the Project in Computing. This study aims to develop a web-based project evaluation and management system named “Evaluation Virtual Assistant” (EVA) to facilitate all users involved in the Project in Computing evaluation process. The prototypes of the proposed system will be developed using XAMPP. Typically, there are four evaluation phases in the Project in Computing, which are proposal, article, presentation, and final report. There were two evaluators that will evaluate both the proposal and article. Another two evaluators will evaluate the presentation, while the supervisor will evaluate the final report. In the proposal and article evaluation, the evaluators should also provide recommendations. Students need to update the proposal and article based on the recommendations. After the evaluators and supervisor completed the evaluation phase related to them, the coordinator can view the total marks obtained by students and proceed to finalize the mark. This web-based project evaluation and management system could speed up the evaluation process while improving efficiency and accuracy of the marking task.